1997
DOI: 10.1038/bjc.1997.244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of δ-aminolaevulinic acid and its methyl ester as an inducer of porphyrin synthesis in cultured cells

Abstract: Summary This study was carried out to test the hypothesis that induction of intracellular porphyrin synthesis by 6-aminolaevulinic acid (ALA) used to sensitize cells in photodynamic therapy would be more efficient if the ALA was used in an esterified form. Contrary to expectation, the generation of tetrapyrroles (TP) by cultured epithelial cells (CNCM-1-221) exposed to equimolar concentrations (0.6 mM) of ALA or its methyl ester (ALA-ME) showed that the mean total TP production rate during 6 h incubation in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 8 publications
2
26
0
1
Order By: Relevance
“…One of the advantages of lipophilic ALA ester (MAL) is its ability to display enhanced penetration into the cell which is contributed by different uptake mechanisms including active transporters of non-polar amino acids or by diffusion while ALA is taken up by bamino acids and g-aminobutyric acid (GABA) [19][20][21]. MAL was eliminated faster than ALA in cultured epithelial cells [22] which coincided with our results. However, our results were contradictory to Casas et al where less ALA was needed than MAL for the formation of PPIX in murine mammary adenoma carcinoma cell line, LM2s [23].…”
Section: Discussionsupporting
confidence: 93%
“…One of the advantages of lipophilic ALA ester (MAL) is its ability to display enhanced penetration into the cell which is contributed by different uptake mechanisms including active transporters of non-polar amino acids or by diffusion while ALA is taken up by bamino acids and g-aminobutyric acid (GABA) [19][20][21]. MAL was eliminated faster than ALA in cultured epithelial cells [22] which coincided with our results. However, our results were contradictory to Casas et al where less ALA was needed than MAL for the formation of PPIX in murine mammary adenoma carcinoma cell line, LM2s [23].…”
Section: Discussionsupporting
confidence: 93%
“…demonstrated in cell lines and animal models, that several ALA pro-drugs were capable of being taken up, desterified and converted into PpIX with higher efficiency than ALA itself. Gaullier and collaborators [20] found that longchained ALA esters (C 6 -C 8 ) reduced 30-150-fold the amount of ALA needed to reach the same level of PpIX accumulation as compared with that obtained with nonesterified ALA in a human cell line, whereas short-chained pro-ALAs (C 1 -C 3 ) were less efficient than ALA. Washbrook and Riley [21] also found the methyl short-chained ester of ALA (1) to be less efficient than ALA itself at inducing porphyrin synthesis in epithelial cells.…”
Section: B Ala Estersmentioning
confidence: 93%
“…Non-specific esterase activities in tissue homogenates, lysates of cultured cells and in cell-conditioned or fresh culture medium were determined using an adaptation of the fluorescein diacetate method described by Washbrook and Riley (1997).…”
Section: Non-specific Esterase Assaymentioning
confidence: 99%